Agriculture, climate change and food security in the 21st century : our daily bread - Ziska, Lewis H. (Cambridge Scholars Publishing, 2017)
"With the global adoption of the 'green revolution' in the 1970s, the long historical legacy of agriculture's boom and bust cycle seemed - finally - to be put on hold. It appeared as though the apocalyptic nightmare of famine had been vanquished. However, now, man-made climate change poses a new and immediate crisis - from Syria to South Sudan - how do we feed the 10 billion people likely to inhabit the planet by 2050? How do we continue to feed, sustainably, the 7.5 billion of us that are already here? How do we do so in a climate that is becoming increasing hostile to food security? This book explores the history of agriculture, and the threat that climate change imposes for all aspects of our 'daily bread'. While these challenges are severe and significant, it argues that we are not without hope, and offers a wide range of solutions, from polyculture farming to feminism that can, when applied, lead to a better future for humankind."--